Primulina porphyrea (Gesneriaceae), a new species from southern Hunan, China - Li, Ming; Yu, Xun-Lin (Phytotaxa, 2015)
A new species of Gesneriaceae, Primulina porphyrea, is described and illustrated from southern Hunan, China. The new species resembles P. polycephala and P. yangshuoensis in leaf blade shape and indumentum of the plants, but it can be easily distinguished by having long petiole and purple leaf abaxial surface, purple corolla lobes and yellow corolla tube with several reddish-purple stripes, dark yellow filaments, and 3 staminodes. It flowers from May to August.